Peran Konselor Dalam Mengembangkan Keterampilan Sosial Siswa SMP - Wulansari, Peppy Sisca Dwi; Khariroh, Nur (Universitas Muria Kudus, 2018)
This study aims to explain 1) understanding of the counselor about the importance of social skills in students; 2) the role of counselors in designing counseling and guidance services to develop students' social skills; 3) implementation of counseling and guidance services conducted by counselors who can develop students' social skills; 4) assessment by counselors in the implementation of services that can develop students' social skills. This research uses qualitative method with descriptive analysis type and case study design. The results showed: Understanding the counselor about skills is still lacking, the counselor sees social skills in terms of communication and cooperation among friends; Prota, RPLBK, Media and Personal Guidance Schedule designed by counselors have not led to the development of social skills as a whole but more focused on personal guidance; the implementation of counseling and guidance services has not implemented services that can develop the maximum social skills; assessment that has been planned and established by the counselor in RPLBK is the assessment of the process and the results can not be done, because RPLBK can not be implemented maximally.